Strategický rozvoj území v kontextu politiky EU - Pospíšilová, Radka (Vysoké učení technické v Brně. Fakulta stavební)
Bakalářská práce řeší téma rozvoje území v kontextu politiky EU. Předmětem teoretické části práce je oblast investic a jejich financování, hospodaření municipalit, politika EU a dotační programy pro období 2014 – 2020. V praktické části je rozebrána investice do rekonstrukce dopravního terminálu ve městě Holešov. Obsahuje také alternativy financování investice. Závěrem je shrnutý vliv investice na rozvoj území.

The bachelor thesis deals with territorial development in the context of EU policy. The subject of the theoretical part of the thesis is the sphere of investment and their financing, management of municipalities, EU policy and subsidy programs in the period 2014 – 2020. The practical part analysis the investment in the reconstruction of the transport terminal in the town Holešov. It also includes alternatives to investment financing. Finally, an effect of the investment on the development of the territory is summarized.
Strategic development of the territory in the context of EU policy
Keywords: Investice; financování investic; hospodaření obcí; politika EU; dotační programy.; Investment; financing investment; management of municipalities; EU policy; subsidy programs.